'Sea of trapezoids': the analytic setting and virtual treatment during a pandemic. Issue 3 (1st September 2020) - Garcia, Michael
ABSTRACT: The Covid-19 global pandemic has, for the moment, upended the traditional setting for analysing transference and countertransference dynamics, vital components to the work of psychoanalytic child psychotherapy. The physicality of the customary treatment setting provides a basis for the experiences of containment and understanding, along with the corresponding and familiar technical considerations within that setting. The absence of these fixed physical elements when transferring cases to virtual and other non-conventional settings points to a new set of technical challenges. How do we understand projective identification, transference and countertransference with children when the modified setting does not inherently afford a child the physical means to make contact with the consulting room as a container? What resources do we have as clinicians for persevering through the psychoanalytic process, in the face of the current global uncertainties? In this paper, I outline some of the theoretical underpinnings in psychoanalytic child psychotherapy that elucidate the challenges to the work I have encountered with my child patients during the pandemic, and explore the clinical implications stemming from those challenges.